Community Empowerment As a Process: A Case Study On Beff Cattle Breeder Empowerment Trough Corporate Social Responsibility (CSR) IN PT. Perkebunan Nusantara XII, Eats Java, Indonesia - Likah, Sad; Soemanto, RHB; Kartono, Drajat Tri; Ratriyanto, Adi (Advances in Social Sciences Research Journal, 2017)
ABSTRACT The process of community empowerment can not be seen only as a means to achieve the goal, but becomes an important goal. Community empowerment is a process in itself. The empowerment process should involve the community. Stages of empowering are training, visits and assistance are quite participative, not accompanied by enabling stages (identification of potential and problems and socialization) are participatory. Full participation at the enabling stage is constrained by cost efficiency and predetermined time limits. The scope of empowerment is still based on the strengthening of economic capital by granting loans for the purchase of livestock germs and human capital with counseling and training. While the strengthening of physical capital, nature and social has not received serious attention. Institutions that are formed have not been able to unite the breeders in order to improve the livestock business more productive and efficient together. Internal CSR with facilitators from the internal company is more efficient and the company's interests can be accommodated, but lack of technical mastering of farms.